(untitled) (Architecture Image Studies, 2025)
This systematic review aims to identify ways to collaborate effectively. Guided by the PRISMA 2020 methodology, it analyzes consensus-building strategies in situations involving governance, citizen participation, social growth, and teamwork. To this end, the 10 most relevant texts were selected from databases such as Scopus, SciELO, Redalyc, Dialnet, Latindex, ERIC, ALICIA Concytec, and the César Vallejo University Library. After an exhaustive search, the first 1,285 data points were obtained, which were re-analyzed, and inclusion and exclusion criteria were applied to reduce the number of articles. The results show that historical consensus-building mechanisms, such as the Contadora Group, and newer ones, such as the Pacific Alliance and CELAC, remain in place. These mechanisms contribute to consensus-building, business, and the coordination of plans among key actors to overcome challenges such as poverty, unifying economies, and bridging border issues. Therefore, coordination among many countries or the creation of support groups is a priority. The objective was to answer the question: What are the most effective strategies for achieving citizen participation documented in the literature of the last five years? The data collection involved different countries, variables, methods, and outcomes. Finally, a narrative discussion was presented, along with several recommendations tailored to the specific situation. This approach ensures transparency and the replicability of the results, enabling the design of public policies that include stakeholders from across the region.